2020
DOI: 10.1093/mnras/staa997
|View full text |Cite
|
Sign up to set email alerts
|

Blazar variability power spectra from radio up to TeV photon energies: Mrk 421 and PKS 2155−304

Abstract: We present the results of the power spectral density (PSD) analysis for the blazars Mrk 421 and PKS 2155−304, using good-quality, densely sampled light curves at multiple frequencies, covering 17 decades of the electromagnetic spectrum, and variability timescales from weeks up to a decade. The data were collected from publicly available archives of observatories at radio from OVRO, optical and infrared (B, V, R, I, J, H, and K-bands), X-rays from the Swift and the Rossi X-ray Timing Explorer, high and very hig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 104 publications
2
24
0
Order By: Relevance
“…Our results are consistent with Bhatta & Dhital (2020), except for 3C 454.3, for which the authors reported β = 1.3 ± 0.17, while we obtained β ∼ 2. Finally, regarding Mrk 421 and PKS 2155−304, we obtained values broadly consistent with those of Goyal (2020).…”
Section: Summary Of Resultssupporting
confidence: 80%
“…Our results are consistent with Bhatta & Dhital (2020), except for 3C 454.3, for which the authors reported β = 1.3 ± 0.17, while we obtained β ∼ 2. Finally, regarding Mrk 421 and PKS 2155−304, we obtained values broadly consistent with those of Goyal (2020).…”
Section: Summary Of Resultssupporting
confidence: 80%
“…PSDs were well fitted with power-law, and their slopes were found in the range of 2.1-2.3 [109]. PSD analysis of long term Swift X-ray observations of PKS 2155-304 fitted well with power-law, and its slope was found to be 1.3 ± 2.1 [65].…”
Section: Power Spectrum Analysismentioning
confidence: 75%
“…PSD analysis of long term RXTE and Swift X-ray observations of Mrk 421 were well fitted with power-law. For RXTE and Swift X-ray light curves, the PSD slopes were found to be 1.1 ± 1.6 and 1.3 ± 0.7, respectively [65].…”
Section: Power Spectrum Analysismentioning
confidence: 95%
“…No significant distinctive differences are present among the different test cases. This indicates that the one-zone emission model might be incapable of producing light curve variability that posses different PSD indices for different wavebands (Goyal 2020).…”
Section: Discussionmentioning
confidence: 99%